Surfactants and polymers on nanoscale surfaces: the interface landscape of plasmonic nanostars - Ferrari, Debora; Deriu, Chiara; Fabris, Laura (Frontiers in Nanotechnology, 2024)
Surfactants and polymers are widely used as shape-directing agents in the synthesis of colloidal plasmonic nanostars, consequently acting as non-negligible players in all those high-performance applications in which processes occur at their interfaces, such as surface enhanced Raman spectroscopy (SERS) and plasmon-induced catalysis. Therefore, elucidating surfactant- and polymer-metal interactions is critical to rationally improving the performance of nanostars in the same range of applications. In this mini-review, we present traditional and state-of-the-art characterization methods that can be used to investigate the ligand-surface interactions that occur on mature nanostars. Due to historically based limitations in the availability of nanostar-specific literature, we utilize nanorod literature as a starting point to critically infer which analytical approaches can be seamlessly translated to nanostar systems, and which instead need to be adapted to intercept the peculiar needs imposed by the branched nanoparticle morphology.